2019
DOI: 10.1177/2047173419870053
|View full text |Cite
|
Sign up to set email alerts
|

SaveWise: The design of a financial education program in the Netherlands

Abstract: Using a framework for educational design research, this article reports and evaluates the (process of the) design of a financial education program. The program is designed for high school students in the prevocational track in the Netherlands. The aim of the program is to improve students’ financial knowledge, attitudes, self-efficacy, and (savings) behavior. The main outcome of this study is the identification of design principles that can be used by others for the design of financial education programs: sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
3
7
0
Order By: Relevance
“…This mindset should benefit them in both their behaviour and in their future teaching. This finding is consistent with the research of Amagir et al (2019).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This mindset should benefit them in both their behaviour and in their future teaching. This finding is consistent with the research of Amagir et al (2019).…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, previous research has found that ICT benefits learners (Gaboy et al, 2020), particularly in financial literacy (Amagir et al, 2019), which is consistent with the results of this study. Both types of research addressed visual aids, as well as videos that can help people to learn more about money.…”
Section: Discussionsupporting
confidence: 93%
“…Besides that, financial education has become a cognitive approach to facilitate the students' learning process and provide more practical experience in supporting influential learning theories (Berková & Krpálek, 2017). The financial literacy program may promote positive changes to the students in terms of financial literacy, economic behavior, and financial competency (Kalwij et al, 2019;Amagir, Groot, Maassen van den Brink, & Wilschut, 2018;Amagir et al, 2019;Zakaria, Sabri, & Rahim, 2017;Bhattacharya et al, 2016;Supanantaroek et al, 2017). However, the studies measure mainly short-term effects.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, most quantitative studies measure financial education initiatives' impact using quasi-experimental designs and randomized controlled trial (RCT) experiments. Amagir et al (2019) conduct a financial education program named "SaveWise" to enhance high school students' financial knowledge and skills, attitudes, self -effectiveness, and economic behavior. It consists of 8 lessons of 50 minutes that focus on learning.…”
Section: Effective Methods To Enhance the Student's Financial Literacymentioning
confidence: 99%
“…The literature on financial literacy indicates that digital tools such as videos, games, cartoons, movies and others could enhance financial literacy effectively (Ferreira and Bisognin, 2020; Popovich et al , 2020; Amagir et al , 2019; Kuntze et al , 2019; Angel, 2018; Kalmi, 2017; Lusardi et al , 2015). Of these tools, video is the most effective in promoting financial literacy among students.…”
Section: Literature Reviewmentioning
confidence: 99%